Comparative analysis of the feasibility of oil palmbiomass and factory tea waste as biosorbent for copper ions removal from wastewater - Tan, Patrick Peng Jun; Tun Izhar, Tun Faralyssa Qistina; Wan Osman, Wan Nur Aisyah; Samsuri, Shafirah; Md Saad, Juniza; Yáñez, Eduard Hernández; Zhou, Hui (UTP Press, 2022)
Numerous research have been conducted to produce low-cost biosorbents. Because of this, this study aims to analyse the feasibility of Oil Palm Biomass (OPB) and Factory Tea Waste (FTW) as the biosorbent for fixed-bed adsorption column system in removing copper ions from wastewater under two parameters: initial concentration and pH value. Both biosorbents were compared in their surface area, pore volume, width and diameter. They were then analysed regarding their isotherm behaviour. FTW is found to have a larger surface area, pore volume and pore width, while OPB has a larger pore diameter than FTW. Besides, OPB showed higher efficiency of copper ions removal at low initial concentrations (25 and 50 mg/L), but FTW was more effective for high initial concentrations (100, 150 and 200 mg/L). FTW was more favourable than OPB in acidic and alkaline conditions, but the copper ions removal efficiency was over 99% for both biosorbents when operating at pH 7 of solution. Furthermore, it was proven that both biosorbents showed a better fit to Langmuir Isotherm as the R2 for both showed the highest value. In conclusion, this study suggested that FTW provided better performance in copper ions removal than OPB.